Analisa Struktur Bangunan Mixed Use Al-Amin Living Lab Dan Industrial Park Di Desa Sampe Cita, Kecamatan Kutalimbaru - Siregar, Hendra Fahruddin; Subarna, Dadang; Andriana, Melly; Purba, M. Ali Tami (Universitas Medan Area, 2024)
A mixed-use building refers to a combination of several different functions within a single structure, such as residential, office, shopping, and recreational functions built on one site. Designing a mixed-use building requires careful planning and consideration of various factors such as functional needs, aesthetics, and energy conservation. Additionally, the design of mixed-use buildings incorporates various functions within a single area. Floor slabs and beams use plain reinforcing steel with a quality of Fy = 240 MPa (Ø8mm). The concrete cover is taken as 20 mm. From the design results, several thickness types of slabs were obtained according to the load requirements that must be accommodated above them. The following are the moments acting on the floor slabs and beams. The reinforcement calculations are performed using the capacity strength design method according to SNI 2847-2019. The capacity design concept involves controlling the formation of plastic hinges at predetermined locations. The SAP2000 program can directly calculate the feasibility of the structural dimensions and the amount of reinforcement needed from the input program results. In the SAP2000 program, the concrete code used is the American concrete code ACI-318-05/IBC 2003, which differs in some respects from the concrete code in Indonesia SNI 2847-2019. Adjustments need to be made to comply with the regulations in Indonesia. Internal forces from the SAP2000 program are selected from load combinations that generate the maximum moments at the column face. The flexural and shear reinforcement for beams can be directly read from the SAP2000 output in the form of information on the required area of reinforcement